2014
DOI: 10.1128/aac.03921-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Binding Sites for Candida glabrata Pdr1 Transcription Factor in Wild-Type and ρ 0 Cells

Abstract: The fungal pathogen Candida glabrata is an emerging cause of candidiasis in part owing to its robust ability to acquire tolerance to the major clinical antifungal drug fluconazole. Similar to the related species Candida albicans, C. glabrata most typically gains azole tolerance via transcriptional induction of a suite of resistance genes, including a locus encoding an ABCG-type ATPbinding cassette (ABC) transporter that is referred to as CDR1 in Candida species. In C. glabrata, CDR1 expression is controlled pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…The fact that in previous genome-wide expression analysis of fluconazole response in C. glabrata the regulation of CgFLR1 or CgFLR2 by CgPdr1 had not been identified suggests that this effect may be specific to imidazole antifungals, such as clotrimazole, but not to triazole antifungals such as fluconazole. Despite the fact that a previous ChIP experiment probing CgPdr1 targets in ρ0 C. glabrata cells did not pinpoint CgFLR1 or CgFLR2 promoters as targets of CgPdr1 (Paul et al, 2014), a putative CgPdr1 binding site can be found in the promoter region of CgFLR2 . The possibility, however, that CgPdr1 may regulate the expression of CgFLR1 and CgFLR2 in clotrimazole stressed cells through direct binding to their promoter regions remains to be established.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The fact that in previous genome-wide expression analysis of fluconazole response in C. glabrata the regulation of CgFLR1 or CgFLR2 by CgPdr1 had not been identified suggests that this effect may be specific to imidazole antifungals, such as clotrimazole, but not to triazole antifungals such as fluconazole. Despite the fact that a previous ChIP experiment probing CgPdr1 targets in ρ0 C. glabrata cells did not pinpoint CgFLR1 or CgFLR2 promoters as targets of CgPdr1 (Paul et al, 2014), a putative CgPdr1 binding site can be found in the promoter region of CgFLR2 . The possibility, however, that CgPdr1 may regulate the expression of CgFLR1 and CgFLR2 in clotrimazole stressed cells through direct binding to their promoter regions remains to be established.…”
Section: Discussionmentioning
confidence: 85%
“…Considering an at least 1.5-fold difference in protein expression activation in wild-type vs. Δ cgpdr1 cells exposed to 5-flucytosine, nine proteins were found to be repressed by CgPdr1; while eight proteins were found to be activated by CgPdr1 (Table 1). The PDRE loci BCCRYYRGD, TCCRYGGA (Tsai et al, 2010), TCCACGGA, and HYCCGTGGR (Paul et al, 2014), were searched for in the promoters of the referred genes using the PathoYeastract database (Monteiro et al, 2016). Interestingly, considering these 17 proteins, at least one CgPdr1-binding site is found in the promoter regions of nine genes, suggesting the action of CgPdr1 in their expression may be direct.…”
Section: Resultsmentioning
confidence: 99%
“…This resistance might have resulted from overexpression of SNQ2 encoding another ABCtype multidrug-transporter protein, overexpression of TPO3 encoding the MFS-type drug efflux pump (Costa et al, 2014) or mutations in PDR1 encoding the transcriptional activator protein, responsible for controlling the level of expression of genes encoding drug efflux transporters including CDR1 (Paul et al, 2014) or any other mechanism. It should be noted that the slight overexpression of SNQ2 found by Sanguinetti et al (2005) in their C. glabrata azole-resistant clinical isolates not overexpressing CDR1 or CDR2 was not directly correlated with the high level of azole resistance, and no evidence for an important contribution of PDR1 or TPO3 upregulation in the azole resistance of C. glabrata clinical isolates has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…The activating mutations exhibit distinct expression patterns of the downstream effector genes, with the exception of increased expression of CDR1 and PUP1 , and no correlation has been found between location of the mutation and altered gene expression (Tsai et al, 2006, 2010; Ferrari et al, 2009; Caudle et al, 2011; Paul et al, 2011). Among the genes whose pleiotropic drug response element (PDRE) is directly bound by Pdr1 (Paul et al, 2014), only three, the ABC transporters CDR1 (Sanglard et al, 1999), PDH1 ( CDR2 ) (Miyazaki et al, 1998; Sanglard et al, 2001), and SNQ2 (Sanguinetti et al, 2005; Torelli et al, 2008), have been linked directly to azole resistance. Recent work has shown increased expression of four MFS transporters in clotrimazole resistant isolates compared to clotrimazole susceptible clinical isolates.…”
Section: Azole Antifungal Resistance Mechanismsmentioning
confidence: 99%